1995
DOI: 10.1016/0378-1097(95)00214-p
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid consumption by the parasitic, amoeboid protists Entamoeba histolytica and E. invadens

Abstract: Amino acid consumption by Entamoeba histolytica and E. invadens has been measured in order to assess the possible roles of amino acids as energy substrates. Mixtures of amino acids enhanced the growth of the parasites in complex medium and their survival in simple medium. The consumption of several amino acids by the parasites suspended in simple media was greater when glucose was absent, suggesting that they may act as alternative energy sources. Under these conditions, asparagine was consumed extremely rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…These interactions differ from those previously reported for invasive and intracellular pathogens, which induce iNOS expression and NO production after invasion of host cells (18,22,26). Furthermore, the findings with the extracellular pathogen, G. lamblia, suggest a concept that may also apply to other extracellular pathogens, such as Entamoeba histolytica, that consume amino acids in the host microenvironment and where NO constitutes a potent host defense (43,44).…”
Section: Discussionmentioning
confidence: 62%
“…These interactions differ from those previously reported for invasive and intracellular pathogens, which induce iNOS expression and NO production after invasion of host cells (18,22,26). Furthermore, the findings with the extracellular pathogen, G. lamblia, suggest a concept that may also apply to other extracellular pathogens, such as Entamoeba histolytica, that consume amino acids in the host microenvironment and where NO constitutes a potent host defense (43,44).…”
Section: Discussionmentioning
confidence: 62%
“…It was previously reported that amino acids such as aspartate, asparagines, and arginine also serve as an energy source in anaerobic parasitic protists [39].…”
Section: Resultsmentioning
confidence: 99%
“…It is conceivable to assume that TFM is incorporated into the amoebae by amino acid transporter(s). It has also been reported that the parasite incorporates amino acids directly from the culture medium [12]. However, it remains to be clarified whether the TFM derivatives are incorporated via the presumed amino acid transporter(s) or by passive diffusion due to their hydrophobic nature.…”
Section: Resultsmentioning
confidence: 98%